PENGGUNAAN JARGON OLEH KOMUNITAS WARIA DI JEJARING SOSIAL ‘FACEBOOK’ - Jusmianti Garing (Badan Pengembangan dan Pembinaan Bahasa, 2017)
Jargon that used by transgender community in social networking ‘facebook’ is really interesting to understand because the jargon has a form and meaning itself in its disclosure. The research discusses of using of transgender community in social networking ‘facebook’ by using semantic parameter. The research aims to describe the jargon forms that used by transgender community in social networking ‘facebook’ and discusses the type of semantics and changes of meaning generated from the jargons. The method used of this research is qualitative descriptive by using noting and scrutinizing technique. The result shows that there are fifty-three of jargons used by transgender community in social networking ‘facebook’. Those jargons are ate, eke/eike, yey, ses, astajim, mengondek, menyabong, res/ress, le/lek/leee, mawar, ono, seljes/seljong, bo, kulo, lekes, mehong, cuccok, ce, nekk, sindang, ceu, libra, chinese, centes, peges-peges, mekong, tinta, bae, kentilas, heywanat, cacamarica, ojo, polo/polonia, mursid/mursida, bosnia, megang, kereles, kempinsky, endes, sahaja, bue, perez, dese, merongin, malides, mojang, priwi, kinyis-kinyis, cuss, eim/em, say, andbye. The jargons are formed based on the type of semantic, namely lexical meaning, grammatical meaning, denotative meaning, connotative meaning, contextual meaning, situational meaning, and thematic meaning. Furthermore, the jargons have also a relation of meaning and aspect of meaning. The relation of meaning is synonym and antonym, while, the aspect of meaning is feeling, tone, and intention. Then, there are some of jargons that undergo change the meaning, that is total meaning, broad meaning, and using diachronic parameter, such, bosnia, mursid, polo astajim, mawar, and bye.ABSTRAKJargon yang digunakan oleh komunitas waria di jejaring sosial “‘facebook’” sangat menarik untuk dipahami karena jargon tersebut memiliki bentuk dan makna tersendiri dalam pengungkapannya. Bagi orang awam jargon tersebut susah untuk dipahami, hanya komunitas merekalah yang mampu memahami maksud dari jargon yang digunakannya tersebut. Tulisan ini membincangkan tentang penggunaan jargon bahasa waria di jejaring sosial ‘facebook’ dan perubahan makna yang ditimbulkan dari jargon tersebut. Tujuan tulisan ini adalah mendeskripsikan bentuk-bentuk jargon yang digunakan oleh komunitas waria di jejaring sosial ‘facebook’ dan menjelaskan kata-kata apa saja yang mengalami perubahan makna. Metode yang digunakan dalam tulisan ini adalah deskriptif kualitatif dengan menggunakan teknik catat dan simak. Hasil penelitian menunjukkan bahwa terdapat lima puluh dua bentuk jargon yang digunakan oleh komunitas waria di jejaring sosial ‘facebook’, yakni ate, eke/eike, yey, ses, astajim, mengondek, menyabong, res/ress, le/lek/leee, mawar, ono, seljes/seljong, bo, kulo, lekes, mehong, cuccok, ce, nekk, sindang, ceu, libra, chinese, centes, peges-peges, mekong, tinta, bae, kentilas, heywanat, cacamarica, ojo, polo/polonia, mursid/mursida, bosnia, megang, kereles, kempinsky, endes, sahaja, bue, perez, dese, merongin, malides, mojang, priwi, kinyis-kinyis, cuss, eim/em, say, dan bye. Jargon-jargon tersebut dibentuk berdasarkan makna leksikal dan gramatikal. Selanjutnya, jargon yang mengalami perubahan makna adalah astajim, mawar, dan bye.